Safety and Feasibility of a Novel Exoskeleton for Locomotor Rehabilitation of Subjects With Spinal Cord Injury: A Prospective, Multi-Center, and Cross-Over Clinical Trial - Chen, Sijing; Wang, Zhanbin; Li, Yongqiang; Tang, Jiashuai; Wang, Xue; Huang, Liping; Fang, Zhuangwei; Xu, Tao; Xu, Jiang; Guo, Feng; Wang, Yizhao; Long, Jianjun; et al. (Frontiers in Neurorobotics, 2022)
Objective: To evaluate the safety, walking efficiency, don and doff time cost, and user satisfaction of Ai-robot. Design: Prospective, multi-center and cross-over trial. Subjects: Paraplegic subjects (n = 40) with T6–L2 level spinal cord injury. Methods: Subjects who could walk independently using Aiwalker, Ailegs, and hip knee ankle foot orthosis (HKAFO) for 6 minutes within 30 days training underwent 10 sets of tests. In each set, they completed three 6-minute walk test (6MWT) sessions using the three aids in random order. Results: Skin lesions, pressure sores, and fractures, were the main adverse events, likely due to lack of experience in using exoskeleton systems. The mean heart rate increases in the Aiwalker (4.21± 8.20%) and Ailegs (41.81 ± 23.47%) groups were both significantly lower than that in the HKAFO group (62.33 ± 28.32%) (both p < 0.001). The mean 6MWT distances of the Aiwalker, Ailegs, and HKAFO groups were 134.20 ± 18.74, 79.71 ±18.06, and 48.31 ± 19.87 m, respectively. The average donning/doffing time costs for Ailegs and Aiwalker were significantly shorter than that of HKAFO (both p < 0.001). Satisfaction was higher in the Ailegs and Aiwalker groups (both p < 0.001). Conclusion: Subjects with paraplegia below T6 level were able to ambulate safely and efficiently with Ai-robot. The use of Ai-robot should be learned under the guidance of experienced medical personnel.